UJI FITOKIMIA, TOKSISITAS DAN AKTIVITAS ANTIBAKTERI EKSTRAK BERBAGAI FRAKSI DAUN MARA (Macaranga tanarius (L.) M.A) TERHADAP BAKTERI Staphylococcus aureus dan Escherichia coli - Ana Arum Sari; Chairul Saleh; Erwin - (JURNAL KIMIA MULAWARMAN, 2015)
Phytochemical, toxicity and antibacterial activity tests of total extract, fractions of n-heksana, ethyl acetate and ethanol-water from mara leaf (Macaranga tanarius (L.) M.A) from Samboja, East Kalimantan has been carried out. Based on the secondary metabolites phytochemical test of the (Macaranga tanarius (L.) M.A) leaf show that total extract is contain alkaloid, flavonoid, phenolic and steroid. n-hexane fraction is contain alkaloid, flavonoid and steroid. Ethyl acetate fraction is contain phenolic and triterpenoid. Ethanol-water fraction is contain alkaloid and phenolic. Brine shrimp lethality test values obtained Lethal Concentration 50 % (LC50) total extract 23.99 ppm , n-heksana fraction 13,93 ppm, ethyl acetate fraction 468,25 ppm and ethanol-water fraction 283,67 ppm. Antibacteria activity test of extracts for Staphylococcus aureus bacteria (positive Gram) and Escherichia coli (negative Gram) was carried out by paper disc method. The test showed that the most active were ethyl acetate fraction with minimum inhibitor consentration of 0,125- 0,5 % (b/v) which clear zone diameter was 7,25 mm on Staphylococcus aureus bacteria and 6,25 mm on Escherichia coli bacteria.